2019
DOI: 10.1002/mds.27717
|View full text |Cite
|
Sign up to set email alerts
|

Voxel‐based quantitative susceptibility mapping in Parkinson's disease with mild cognitive impairment

Abstract: Objective Brain iron accumulation has been proposed as one of the pathomechanisms in Parkinson's disease (PD). This study aimed to examine the whole‐brain pattern of iron accumulation associated with cognitive impairment in patients with PD using voxel‐based quantitative susceptibility mapping analysis. Methods We enrolled 24 patients with PD and mild cognitive impairment, 22 patients with PD and normal cognition, and 20 age‐matched healthy controls in this cross‐sectional study. All participants underwent glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 49 publications
11
70
1
Order By: Relevance
“…Previous ROI analyses reported increased QSM in bilateral hippocampus and thalamus in PD dementia 22. A recent ROI analysis found increased QSM in PD-MCI (mild cognitive impairment) relative to PD in regions including precuneus and orbitofrontal cortex, and higher QSM with decreasing MoCA in cuneus and caudate nucleus 35. Here we show for the first time that cognitive scores relate to QSM signal detected in a whole-brain analysis.…”
Section: Discussionsupporting
confidence: 63%
“…Previous ROI analyses reported increased QSM in bilateral hippocampus and thalamus in PD dementia 22. A recent ROI analysis found increased QSM in PD-MCI (mild cognitive impairment) relative to PD in regions including precuneus and orbitofrontal cortex, and higher QSM with decreasing MoCA in cuneus and caudate nucleus 35. Here we show for the first time that cognitive scores relate to QSM signal detected in a whole-brain analysis.…”
Section: Discussionsupporting
confidence: 63%
“…Cortical thinning and higher iron burden in this region were observed in PD (including MCI cases) compared with controls and were associated with worse cognitive performances in patients, suggesting this region as vulnerable for patients' cognitive decline. 36,37 Thus, it is possible that thicker cortex manifests early in the disease before giving way to atrophic processes, following an inverted U-shape function. A similar rationale was provided to explain increased cortical thickness and hippocampal and cerebellar volumes in early PD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on PD patients with cognitive impairment describe increased iron accumulation in the caudate and cortex. [191][192][193] Arguing in favor of a causative role for iron in PD are the observations that direct infusion of Fe 3þ to the SN in rats results in mitochondrial dysfunction, oxidative stress, neuronal loss, striatal dopamine depletion, and impaired motor function, all characteristic features of PD. [194][195][196][197] Administration of MPTP or 6-OHDA to rodents and monkeys also increases iron content in the SN and this increase is proportional to the loss of neurons.…”
Section: Age-associated Neurodegenerative Diseasesmentioning
confidence: 99%
“…203 Relevant to this point, some human studies have found that the increase of SN iron occurs only in the most severely affected patients. [189][190][191][192][193][194][195] At least one study utilizing monkeys and the MPTP model also found that the increase of iron in the SN occurs only with severe PD pathology and behavioral deficits. 207 Given that the clinical symptoms, neuropathological features, and rate of disease progression display a significant level of variability, it is possible that in a subset of PD cases, iron accumulation may be causally involved in disease progression, whereas it may be associated or result from degeneration in some other cases of PD.…”
Section: Age-associated Neurodegenerative Diseasesmentioning
confidence: 99%